Considering the efficacy of stress management education on small-town and rural police - Oliver, Willard M. (Applied psychology in criminal justice, 2009)
Previous studies on police stress have focused on both maladaptive and adaptive coping strategies and have consistently made the recommendation that agencies provide stress management programs for their officers. As research into the efficacyof these programs is lacking, this study attempted to address this gap in the literature by assessing the impact of stress management training on officers' anxiety, self-reported levels of stress, and behaviors in a paired sample (pretest/posttest) t-test. Findings suggested that these programs do have an impact on officer stress, but as the lag time increases, there is a diminished return of benefit, supporting the need for continued education.